AB0081 Occupation and Risk of Developing Rheumatoid Arthritis. (15th July 2016) - Ilar, A.; Alfredsson, L.; Wiebert, P.; Klareskog, L.; Bengtsson, C.
Abstract : Background: Due to the proposed etiologic involvement of the lung in the development of rheumatoid arthritis (RA), there is reason to study whether other airborne exposures than smoking and silica dust increase the risk of RA. By finding occupations that are related to RA, we can get a hint of which hazardous agents that may be involved in the disease development. Objectives: The aim of this study was to estimate the association between occupation and the risk of anti-citrullinated protein antibody positive (ACPA+) or ACPA- RA in men and women. Methods: The study was based on the Swedish population-based case-control study Epidemiological Investigation of Rheumatoid Arthritis (EIRA), including men and women aged 18–70 years. Controls were matched to cases on sex, age group and residential area. Participants were enrolled between 1996 and 2014. Self-reported data on occupational history, environmental- and lifestyle factors were collected by a questionnaire. Blood samples were taken at clinics to assess the ACPA status of the cases. We used unconditional logistic regression to assess the odds ratios (ORs) and 95% confidence intervals (CIs) of RA due to last occupation before study inclusion among 3, 557 cases and 5, 665 controls. Occupations were divided into 70 occupational groups and occupations within the professional, technical, administrative, managerial and administrative fields served as the reference group. Crude ORs were adjusted for age group and geographical area, and for the adjusted model we added pack-years of smoking, alcohol use, university degree and BMI. Results: After adjusting for confounding from pack-years of smoking, alcohol use, university degree and BMI, only assistant nurses and attendants in psychiatric care were associated with a significantly increased risk of ACPA+ RA (OR: 1.3, 95% CI: 1.1–1.5). No occupations among women were significantly related to ACPA- RA after adjustment for the confounders. Among men, electrical and electronics workers (OR: 2.1, 95% CI: 1.1–3.7), bricklayers and concrete workers (OR: 2.9, 95% CI: 1.4–5.7) and material handling operators (OR: 2.1, 95% CI: 1.2–3.9) had an increased risk of ACPA+ RA. Electrical and electronics workers (OR: 2.6, 95% CI: 1.3–5.0) as well as bricklayers and concrete workers (OR: 2.6, 95% CI: 1.1–5.9) also had an increased risk of ACPA- RA. Conclusions: Several occupations were related to ACPA+ or ACPA- RA. Mainly occupations within the manufacturing field were related to RA, and fewer women than men were working in this field. Adjustment for pack-years of smoking, alcohol use, university degree and BMI could not explain why certain occupations were related to an increased risk of ACPA+ or ACPA- RA, supporting the theory that there is an involvement from other harmful, occupational agents. Disclosure of Interest: None declared